(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2015)
Since the conception of World Wide Web by Sir Tim Berners-Lee, a lot has been changed. The web has completely revolutionized our lives and it continues to make a profound impact on the world. Today millions of people use web services for communication, online shopping, online banking etc; however web is crippled with its own security issues. Cyber criminals have always posed a serious threat to millions of users who rely heavily on web for their day to day activity and compelling the users to live in complete oblivion of their compromised privacy. So in order to protect the users who repose great trust in e-business from BAD GUYS of cyber world, web security becomes imperative.One of the security aspects of web is Password Authentication and trans fer of data. Several kinds of attacks like Brute Force or Dictionary at tacks can severely breach the privacy of the online users by stealing users credentials, so this paper highlights the innovation in Password Authenti cation using SALT HASHING to prevent time-memory trade-off attacks and there by strengthening the web security.